2012
DOI: 10.3109/07420528.2012.668996
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Variations in Exsorptive Transport: In Situ Intestinal Perfusion Data and In Vivo Relevance

Abstract: The circadian timing system (CTS) governs the 24-h rhythm of the organism and, hence, also main pathways responsible for drug pharmacokinetics. P-glycoprotein (P-gp) is a drug transporter that plays a pivotal role in drug absorption, distribution, and elimination, and temporal changes in its activity may affect input, output, activity, and toxicity profile of drugs. In the current study, the influence of different circadian stages on the overall intestinal permeability (P(eff)) of the P-gp substrates talinolol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 42 publications
1
17
0
2
Order By: Relevance
“…This is in line with several in vitro and in vivo studies that have shown 24-h variation in the expression and activity of P-gp in several different cell types (1015). For example, Okyar et al (2012) found that the activity of P-gp in the intestine is higher during the active period of rats (13). Future studies investigating the activity of P-gp in different cell types of the CNS across the 24-h cycle may provide further information on the molecular mechanisms underlying the findings presented in this study.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with several in vitro and in vivo studies that have shown 24-h variation in the expression and activity of P-gp in several different cell types (1015). For example, Okyar et al (2012) found that the activity of P-gp in the intestine is higher during the active period of rats (13). Future studies investigating the activity of P-gp in different cell types of the CNS across the 24-h cycle may provide further information on the molecular mechanisms underlying the findings presented in this study.…”
Section: Discussionmentioning
confidence: 99%
“…So, all the studies in mice reported the peak of P-gp mRNA and protein expression in the intestine to be in the late sleep phase and in the liver in the early or mid-active phase. In contrast in rats, intestinal secretion of the P-gp substrates talinolol and losartan was greater during nocturnal activity (ZT13-ZT15) than daytime rest (ZT1-ZT3) (30). P-gp rhythm has been investigated also in daytimeactive cynomolgus monkeys (31).…”
Section: Discussionmentioning
confidence: 99%
“…Metabolism and elimination are altered by biological rhythms due to changes in perfusion, glomerular filtration rate, urine excretion rate, urine pH, and electrolyte balances [131,147,148]. Furthermore, circadian rhythms may modulate carrier-mediated transport activity significantly, leading to differences in absorption, intestinal metabolism, or even renal clearance [149,150,133]. Bioavailability of drugs that are P-glycoprotein substrates may have a dependence on circadian rhythms.…”
Section: Model Parameterization For Special Populationsmentioning
confidence: 99%